2005
DOI: 10.1002/rcm.2026
|View full text |Cite
|
Sign up to set email alerts
|

An evaluation of the utility of in vacuo methylation for mass‐spectrometry‐based analyses of peptides

Abstract: In vacuo trimethylation of the N-terminus of a lyophilized peptide with methyl iodide was previously reported to enhance the peptide's signal in matrix-assisted laser desorption/ionization mass spectrometry (MALDI-MS) and to suppress alkali adduct formation in electrospray ionization mass spectrometry (ESI-MS). Both the signal enhancement and alkali adduct suppression observed for methylated peptides are believed to be due to the permanent positive charge on the N-terminus of the peptide resulting from the for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
17
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 27 publications
(49 reference statements)
1
17
0
Order By: Relevance
“…This report describes the utility of the In Vacuo I sotope C oded A lkylation T echnique (IVICAT) as an isotopic N‐terminal label for quantitative proteomic analysis. The ability of H 9 and D 9 N‐terminal trimethylammonium‐derivatized peptides to enhance the detection signal by MALDI‐MS, as previously shown,30, 32 is demonstrated. Furthermore, we describe the fragmentation characteristics of IVICAT‐labeled peptides in collision‐induced dissociation (CID) ESI tandem mass spectrometry (MS/MS) modes.…”
supporting
confidence: 63%
See 1 more Smart Citation
“…This report describes the utility of the In Vacuo I sotope C oded A lkylation T echnique (IVICAT) as an isotopic N‐terminal label for quantitative proteomic analysis. The ability of H 9 and D 9 N‐terminal trimethylammonium‐derivatized peptides to enhance the detection signal by MALDI‐MS, as previously shown,30, 32 is demonstrated. Furthermore, we describe the fragmentation characteristics of IVICAT‐labeled peptides in collision‐induced dissociation (CID) ESI tandem mass spectrometry (MS/MS) modes.…”
supporting
confidence: 63%
“…Recently, the in vacuo trimethylation of peptides with methyl iodide was shown to be a promising approach in labeling of all peptides at their N‐termini for MS 30–32. It was demonstrated that the permanent positive charge induced by the quaternary methylated ammonium group enhanced the detection signal of the labeled versus the non‐labeled peptides in MALDI‐MS 30.…”
mentioning
confidence: 99%
“…Currently, mass spectrometry (MS) based detection techniques have emerged as indispensable tools for peptide analysis [11]. To increase the ionization efficiency of pep-tides (especially for those with low abundance and poor ionization efficiency) by MS, a variety of chemical derivatization reagents [12] that target labeling of the amino group [13][14][15], thiol group [16][17][18] and hydroxyl group [19,20] have been developed. Smith et al applied the aldehydebased derivatization reagent hexanal and butanal for the alkylation of primary amines in peptides to provide an increase in ionization efficiency and concomitant signal enhancement.…”
Section: Citationmentioning
confidence: 99%
“…Moreover, nucleophilic side chain modifications could occur, disturbing subsequent MS identification. Choma et al [25] further evaluated the general utility of iodomethane derivatization for MS-based peptide identification. With the present reaction conditions, although side chain modifications were inevitable, the signal intensity of peptides, especially for those lacking lysine and arginine residues, could be improved via MALDI-TOF MS.…”
Section: Derivatization Of Amino Groupmentioning
confidence: 99%